A 600 mg of fixed‐dose linezolid in renally impaired patients versus 15 mg/kg intermittent dose‐optimized vancomycin in renally non‐impaired patients: A single centre retrospective analysis for adult patients with hospital‐acquired pneumonia due to methicillin‐resistant Staphylococcus aureus. Issue 4 (23rd March 2023) - Wang, Mengqin; Liu, Xiao; Tian, Zhaoxing
Abstract: Objectives: Both linezolid and vancomycin are approved by USFDA and IDSA guidelines for the management of nosocomial pneumonia due to methicillin‐resistant Staphylococcus aureus (MRSA) in clinical practice. Baseline creatinine clearance is the criterion for prescribing vancomycin or linezolid for hospital‐acquired pneumonia in our institution. However, patients with renal function impairment are far more difficult to manage in intensive care. Thus, the objectives of the study were to compare the clinical efficacy and safety of 600 mg of fixed‐dose linezolid with intermittent dose‐optimised vancomycin in hospital‐acquired pneumonia due to MRSA and to evaluate parameters of clinical cure. Methods: Analysis of a review of patients' charts. Patients with creatinine clearance <80 ml/min received 600 mg linezolid/12 h ( n =  139, LN cohort), and patients with creatinine clearance ≥80 ml/min received intravenous 15 mg/kg vancomycin/12 h for 1–2 weeks consecutively or 3 weeks in case of bacteremia ( n =  152, VC cohort) for management of hospital‐acquired pneumonia due to MRSA. Results: A 59% of patients from the LN cohort and 47% of patients from the VC cohort were clinically cured. Administration of systemic steroids ( p  = 0.0412) and ≥ 80 ml/min creatinine clearance ( p  = 0.0498) were the independent parameters for the clinical cure of patients. Nephrotoxicity was higher among patients of the VC cohort than the LN cohort ( p  = 0.0464). Treatment failed in 41% of patients from the LN cohort and in 53% of patients from the VC cohort ( p  = 0.0200). Conclusions: A 600 mg of fixed‐dose linezolid is an ideal alternative to intermittent dose‐optimised vancomycin for better clinical outcomes for patients with hospital‐acquired pneumonia due to MRSA, especially for patients with renal impairment.